BIM in Structural Project: Interoperability Analyses and Data Management - Augusto M. Gomes; Gonçalo Azevedo; Alcínia Zita Sampaio; Alberto Sánchez Lite (Applied Sciences, 2022)
Building Information Modelling (BIM) is a methodology supported on technological evolution achievements, and consists of a set of processes and tools that allows the creation of a digital three-dimensional model. The model centralizes information, in an organized database, facilitating the data access and the exchange between the collaborators and enterprises along all life cycle of a building. The study is focused on the application of BIM within the framework of a structural design, identifying the benefits and limitations verified in the process and indicating strategies allowing to improve the quality of the project and construction. A structural BIM model of a study case was created; using BIM based platforms, followed by its transfer to the calculation software, where the structural analysis and design were carried out. After, using the structural BIM model complemented with the reinforcements, several applications and tasks were performed, namely, the coordination and collaboration procedures, detection of conflicts analyses, production of dynamic drawings, budget estimation and environmental impact simulation of the structural framework concerning the CO2 emission. In the structural domain, the interoperability is the main problem that must be understood and the present study contributes to clarify the recurrent limitations. The research also presents the capacity of BIM methodology of using the database of the BIM model to achieve several types of tasks that normally are associated to the structural design. The study demonstrates the significant improvement in the quality of the structural design and the wide applicability of the BIM model, when compared with the current traditional sequential and fragmented process.